Hubungan Integritas Akademik dengan Motivasi Belajar Mahasiswa Baru Jurusan Pendidikan Ekonomi FKIP UHO - Yuniyarti Ahiri; Jafar Ahiri; Muni Nia; Harjun Harjun; Muhammad Juwantho Lewa; Wahyu Muh. Syata; Ilhamurrahman M Hubaib (Educational Journal, 2026)
Academic integrity and learning motivation are two closely related psychological factors that shape how university students engage with their academic responsibilities. Despite growing awareness of their theoretical connection, empirical research directly examining this relationship among first-year Indonesian university students remains limited. This study investigated the relationship between academic integrity and learning motivation among new students (n = 80) of the Economics Education Department, Faculty of Teacher Training and Education (FKIP), Halu Oleo University (UHO), using a quantitative correlational design with proportional stratified random sampling. Data were collected using the Academic Integrity Scale (α = 0.879; 30 items), based on McCabe et al. (2012), and the Learning Motivation Scale (α = 0.903; 27 items), adapted from Ilham et al. (2022). Prerequisite assumption tests confirmed normality (Asymp. Sig. = 0,163), linearity (Sig. Linearity = 0.000), and homoscedasticity (Glejser Sig. = 0.241). Pearson correlation analysis revealed a strong positive relationship (r = 0.654, p < 0.001). Simple linear regression confirmed that academic integrity significantly predicted learning motivation (B = 0.632, β = 0,654, t = 7.635, p < 0.001), accounting for 42.8% of its variance (R² = 0.428, F = 58.296, p < 0.001). These findings demonstrate that building academic integrity from the very start of undergraduate study is a strategically important step in fostering strong, sustained motivation to learn among new students.